Urgensi Pendidikan Karakter Berbasis Kearifan Lokal Etnis Sasak di Sekolah Dasar - Parhanuddin, Lalu; Nurdin, Encep Syarief; Budimasyah, Dasim; Ruyadi, Yadi (Jurnal Paedagogy, 2023)
This research aims to describe the urgency of character education for students through the values of local wisdom of the Sasak ethnic group. This research used a descriptive method with a qualitative approach. The subjects of this study were education stakeholders at the East Lombok District Education and Culture Office, such as the Elementary School Development Section, the Curriculum Section, the Educators and Education Staff Section, principals, and educators at elementary schools. Interviews, group observation, and documentation carried out data collection techniques. The research data was analyzed by organizing the data into categories, describing them into units, synthesizing them, compiling them into patterns, interpreting them and making conclusions. The results of this study indicated that character education in elementary schools could be carried out in a "hybrid" way, in which the local government enforces a policy (top-down) on education units to "infuse" wisdom values through all school subjects and activities. In addition, the policies taken must also be aligned with the community’s needs regarding the importance of local wisdom values of the Sasak tribe, which must be internalized (bottom-up). Therefore, parents, schools and the government must jointly identify and revitalize the local wisdom values of the Sasak tribe, which will be infused into school culture.